Kinerja Investasi Saham Berkelanjutan Indeks Sri Kehati Dengan Metode Sharpe - Ali Fikri, Muhamad Agung (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2023)
Investors can invest in sustainable stocks through investing in SRI KEHATI index shares. The SRI KEHATI index consists of 25 stocks that carry out ESG principles which are evaluated every semester. After screening, there were 18 stocks that consistently entered the criteria for the SRI KEHATI index during 2022. The results of the performance assessment using the Sharpe method showed that most of the SRI KEHATI index stocks had good performance. Banking sector stocks have the best Sharpe performance compared to other sectors. Of the 18 stocks studied, there are six stocks with negative returns during 2022. This shows that there is no linear relationship between stocks in the same index.